Linum usitatissimum L. seeds: Flax gum extraction, physicochemical and functional characterization. (1st July 2019) - Rashid, Farhat; Ahmed, Zaheer; Hussain, Sarfraz; Huang, Jen-Yi; Ahmad, Asif
Highlights: Flax gum (FG) from local flaxseed was extracted & purified. Explored physicochemical & functional properties of extracted flaxseed gum. Formation of stable oil in water emulsion with maximum stability >90%. GC analysis depicted acidic & neutral behavior of heteopolysaccharid FG. Flax gum attributes depicted a promising candidacy for industrial application. Abstract: Flax gum (FG) was extracted and purified from flaxseed ( Linum usitatissimum L.) locally called as Alsi. Physicochemical and functional aspects of separated gum were interrogated in detail. Fourier Transform Infrared Spectroscopy analysis depicted variety of peaks in region of 3308.8, 2923.60, 1739.97 & 1149.68 cm −1 which are feature of typical polysaccharide. Functional properties of FG depicted higher water holding ability and lower oil holding aptitude compared to reference materials. Foaming capacity, swelling index and foaming stability of FG were 27.5%, 55.0% and 10.5% respectively which were higher than reference gums. Highest emulsion stability was evident at 0.5% concentration >95.Monosaccharide composition depicted the acidic and neural behavior of heteopolysaccharide FG. Thermal analysis revealed that FG was highly stable. XRD analysis depicted amorphous behavior. SEM imaging indicated a splendor and shiny surface of FG. In conclusion, FG is suitable for variety of food formulations as a thickener, stabilizer, and moisture-retaining agent.